Avaliação da transferência de imunidade passiva em cordeiros com até 30 dias de idade - Féres, Flávia Corbari [UNESP] (2010)
The aim of this study was to determine the serum concentrations of immunoglobulin G, TP and the γ globulin electrophoretic fraction, as well as the enzymatic activities of GGT and ALP. This was done in order to explore the possibility of using changes in activities of these enzymes as indirect indicators of adequate humoral immunity and/ or failure of immune passive transfer in lambs. Pearson correlation was performed between variable of four groups of age during the first 30 days of life. Blood samples (191) from lambs from 21 different farms in Araçatuba region- São Paulo. The following tests were perfomed: radial immunodiffusion, spectrophotometry and electrophoresis to stain the amount of IgG, TP and γ globulin, respectively. GGT and ALP values were determinate using commercial kits. There was a statistically significant correlation between ALP and GGT. The same correlation was observed from TP, IgG and GGT. A positive γ globulin correlation was found between GGT, IgG and TP. ALP activity cannot be used as an indicator of immune passive transfer.